A Review of the Different Sensors for the Detection of Rice Rancidity Indicators - Joseph R. Ortenero; Angelo Earvin Sy Choi; Mariafe S. Calingacion (Chemical Engineering Transactions)
Rice loss occurs in various supply chain stages ranging from harvesting to consumption. Within this chain, rice is handled and stored by farmers, distributors, and vendors, not all of whom would likely have access to sophisticated storage facilities and management processes. Non-ideal storage conditions can lead to rancidity – the spoilage of food to such an extent that it becomes undesirable or even unsafe for consumption. To reduce the wastage of rice during warehousing and storage, sensors that will monitor the onset of rancidity are necessary to mitigate losses associated with spoilage. This work summarizes the different sensors that have been developed to detect the onset of rancidity in rice. Various types are discussed, as well as the corresponding parameters that affect the sensor response, detection limit, and sensitivity. Polymer-based sensors are superior to transition metal-based sensors with a polymer complex that can detect up to 0.05 ppm of hexanal and has the best performance reported in the literature. Recent developments are elucidated as to their application in improving the monitoring of rice conditions during warehousing, storage, and transportation.